How can good general practitioner care be achieved?. Issue 6565 (17th January 1987) - Morrell, D C; Roland, M O
Abstract : It has been shown that to provide a high standard of care general practitioners probably need to book consultations at intervals of at least 10 minutes. In this study the maximum list size for which a general practitioner might be expected to provide a high standard of care was determined from calculations of the time spent consulting, based on various consultation rates and list sizes and assuming that consultations were 10 minutes long. If good quality care is to be provided and is to include the range of services suggested in the government's recent green paper average list sizes should probably be no more than 1750, and lower in areas of high demand and high need. In addition to this, minimum standards could be determined for such measures as facilities available in surgeries, practice records, and accessibility of doctors to ensure that basic services were offered by all general practitioners.